R&D Appropriability, Opportunity, and Market Structure: New Evidence on Some Schumpeterian Hypotheses - Levin, Richard C.; Cohen, Wesley M.; Mowery, David C. (American Economic Review, 1985)
One of the largest bodies of literature in the field of industrial organization is devoted to the interpretation and testing of several hypotheses advanced by Joseph Schumpeter (1950) concerning innovation and industrial market structure. One set of hypotheses focuses on the role of firm size as a determinant of R&D spending and the rate of technological advance. Another set focuses on the effect of market concentration on R&D and technological advance. In this paper, we reexamine the latter set of hypotheses at the industry level, using new data on R&D appropriability and technological opportunity collected by Levin et al. (1984) in a survey of R&D executives in 130 industries.